Bile acids regulation of cellular stress responses in liver physiology and diseases - Tiangang Li; Mohammad Nazmul Hasan; Lijie Gu (eGastroenterology)
Bile acids are physiological detergents and signalling molecules that are critically implicated in liver health and diseases. Dysregulation of bile acid homeostasis alters cell function and causes cell injury in chronic liver diseases. Therapeutic agents targeting bile acid synthesis, transport and signalling hold great potential for treatment of chronic liver diseases. The broad cellular and physiological impacts of pharmacological manipulations of bile acid metabolism are still incompletely understood. Recent research has discovered new links of bile acid signalling to the regulation of autophagy and lysosome biology, redox homeostasis and endoplasmic reticulum stress. These are well-conserved mechanisms that allow cells to adapt to nutrient and organelle stresses and play critical roles in maintaining cellular integrity and promoting survival. However, dysregulation of these cellular pathways is often observed in chronic liver diseases, which exacerbates cellular dysfunction to contribute to disease pathogenesis. Therefore, identification of these novel links has significantly advanced our knowledge of bile acid biology and physiology, which is needed to understand the contributions of bile acid dysregulation in disease pathogenesis, establish bile acids as diagnostic markers and develop bile acid-based pharmacological interventions. In this review, we will first discuss the roles of bile acid dysregulation in the pathogenesis of chronic liver diseases, and then discuss the recent findings on the crosstalk of bile acid signalling and cellular stress responses. Future investigations are needed to better define the roles of these crosstalks in regulating cellular function and disease processes.